Antiviral Activity of Arabinosyladenine and Arabinosylhypoxanthine in Herpes Simplex Virus-Infected KB Cells: Selective Inhibition of Viral Deoxyribonucleic Acid Synthesis in Synchronized Suspension Cultures - Shipman, Charles (1976)
The drug 9-β-d-arabinofuranosyladenine (ara-A) significantly suppressed the formation of herpes simplex virus type 1-induced syncytia in BHK-21/4 cells at concentrations as low as 0.1 μg/ml. Optimal activity was noted when the drug was added before initiation of viral deoxyribonucleic acid (DNA) synthesis (3.5 h postinfection). The deaminated derivative of ara-A, 9-β-d-arabinofuranosylhypoxanthine (ara-H), was at least 10 times less effective in suppressing the development of herpes simplex virus-induced syncytia. The replication of herpes simplex virus was measured by assaying fluids and cells from infected drug-treated cultures by using a plaque production technique. Ara-A at drug levels of >10 < 32 μg/ml completely blocked the replication of infectious virus particles. Ara-H was less effective than ara-A in reducing the replication of virions. Rates of host and viral DNA synthesis were monitored by pulse labeling herpes simplex virus-infected synchronized KB cells with [(3)H]thymidine and subsequently separating viral from cellular DNA in CsCl density gradients. During synthetic (S) phase, ara-A or ara-H at concentrations ranging from 3.2 to 32 μg/ml selectively inhibited viral DNA synthesis. At 3.2 μg of ara-A per ml, viral DNA synthesis was reduced 74% although total cellular DNA synthesis was unaffected. Increasing concentrations of ara-A produced increasing temporal delays in the maximal rate of host DNA synthesis. This time shift was not observed in cells treated with ara-H.